BAG3 attenuates tau hyperphosphorylation and gliosis induced by traumatic brain injury. (20th December 2022) - Morrison, Cody; Li, Liangping; Liang, Jiawen; Chen, Shuo; Acosta, Diana M; Fitzgerald, Julie A; Karelina, Kate; Bray, Chelsea E; Weil, Zachary M; Godbout, Jonathan; Kokiko‐cochran, Olga N; Saito, Takashi; et al.
Abstract: Background: Alzheimer disease (AD) and traumatic brain injury (TBI) are two devastating brain disorders with complex relationships. Growing evidence supports that early or middle life of TBI may be a risk factor for developing late‐life AD and AD‐related dementias (ADRD). Tau hyperphosphorylation and gliosis may serve as a causative link between TBI and AD as well as ADRD. We have recently identified BCL2 associated athanogene 3 (BAG3) as a hub gene of regulating tau protein homeostasis. The protein level of BAG3 is significantly reduced in neurons, but it is increased in astrocytes of human AD compared to controls. We hypothesized that overexpression of BAG3 in neurons would attenuate tau hyperphosphorylation and gliosis induced by TBI. Method: We injected 500 nL AAV9‐hSYN1‐eGFP‐2A‐hBAG3‐WPRE or AAV9‐hSYN1‐eGFP‐WPRE (control AAV9) into the hippocampal CA1 and DG regions of C57BL6/J and htau knock‐in mice. These mice were subjected to TBI surgery (controlled cortical impact, velocity: 3.00 m/s, depth: 0.8 mm, dwell time: 200 ms) three months post the injection. We then performed behavioral tests (open‐field test, Y‐maze, and Morris Water Maze) on these mice one month after the CCI surgery. Following the behavioral tests, we collected the brain tissues and performed the immunofluorescent staining of ptau (PHF1, pS396/404 tau), BAG3, IBA‐1 (microglia/macrophage marker) and GFAP (astrocyte marker) on fixed mouse brain floating sections. Result: TBI increased the immunoreactivity of PHF1, IBA‐1, GFAP and astrocytic BAG3, whereas reducing neuronal BAG3 compared to sham C57BL6/J and htau knock‐in mice. Furthermore, the immunoreactivity of BAG3 increased, while PHF1, IBA‐1 and GFAP decreased in the ipsilateral hippocampus after the injection of AAV9‐BAG3 compared to those TBI mice injected with control AAVs. Continued immunofluorescent staining and quantification for AAV9‐BAG3‐ and control AAV9‐injected mice is currently ongoing, as is behavior data quantification. Conclusion: TBI induces tau hyperphosphorylation, microglia activation and reactive astrocytes, while reducing neuronal BAG3 in C57BL6/J and htau knock‐in mice. Neuronal overexpression of BAG3 can significantly attenuate tau hyperphosphorylation and gliosis induced by TBI. Our data suggests that targeting neuronal BAG3 may be a therapeutic strategy for preventing or reducing intra‐neuronal tau aggregates and gliosis found in TBI and TBI‐associated AD and ADRD.